Trends and Issues in Contemporary Arab Thought (American Journal of Islam and Society, 1991)
The author, Issa Boullata, states that his intention is to study Arabintellectual and social phenomena and trends against the background ofmodernity: “Particularly insufficient in Western studies are publications onArab intellectuals who are grappling with the idea of modernity” (p. ix).Furthermore, “this book, concerned with the present-day Arab culture andits crisis, will attempt to present a number of important themes that haveengaged Arab intellectuals” (p. 9) who “exhibit a profound desire to grapplewith the problem of modernity” (p. 2).Boullata uses two essential terms in his study- modernity andmodernization - without exploring their epistemological structure and meaning,historical formation (especially in the context of Europe), and social viabilityin the modern Arab world. He takes it for granted that the Arab world hasbeen a part of the modernization process for many decades. Furthermore,he seems to make a distinction between two types of Arab intellectuals:progressive/modernizing (forces of modernity), and conservative/traditionalist(forces of tradition). He claims that the first type “voiced and articulatedthe frustration of the Arab masses against Arab regimes and the prevalentculture of Arab society. Their writings were characterized by deep socialinsight, self-analysis and a great measure of self-criticism” (p. 2). And, “themore progressive among Arab intellectuals have tried to analyze the relationshipof contemporary Arabs and the West” (p. 8). Also, “the forces of modernity,using mostly external ideas and models for change, are oriented towards thefuture, which they see as opening new horizons for the Arabs. Opposingthem the forces of tradition, using mostly internal ideas and models for change,are oriented towards the past, which they see as an ideal to be repted becausethey perceive it as having the promise of certainty and surety of proven success”(p. 6). Finally, “The difference between the extremist Arab thinker on theRight and the extremist Arab thinker on the Left is that the former conformsto a past-oriented ideology which he believes originates in God and divine ...